Landscape heterogeneity increases bird functional diversity within Neotropical vineyards - Moreno, Daniele J.; Ribeiro, Milton C. [UNESP]; Piratelli, Augusto J. (Wiley, 2024)
Conversion of lands to agroecosystems has resulted in a decline in bird biodiversity. Analyzing functional diversity is a central tool for detecting changes in the ecological functions performed by birds in these landscapes. This paper aims to investigate the responses of bird taxonomic and functional diversity to landscape heterogeneity and native forest cover in Neotropical vineyards. We sampled 19 vineyard landscapes in southeastern Brazil. These landscapes covered a gradient of forest cover and heterogeneity resulting from various land-uses. To assess bird diversity, we considered both taxonomic diversity and functional diversity (i.e., functional richness, evenness, and divergence). To examine the potential interactions between landscapes and bird assemblages, we employed generalized linear models (GLM). Taxonomic diversity showed no correlation with any landscape metrics. On the other hand, variation in the three metrics of functional diversity was related to landscape heterogeneity. However, in heterogeneous landscapes, these communities can be structured by limiting similarity processes. We highlight the negative impact of landscape homogenization on the ecological functions performed by birds in vineyards, while finding no significant effect on species diversity. These findings can provide valuable support for the formulation of public policies aimed at striking a balance between agricultural production and biodiversity conservation. Abstract in Portuguese is available with online material.
Keywords: agroecosystems; Atlantic forest; biodiversity hotspot; bird communities; ecological functions; land-use impacts